Cerebral equine hydatidosis in Southern Brazil - Ruas,Jerônimo Lopes (1997)
Equine cerebral hydatid disease is described in a 7-year-old, crossbred, female horse. Clinical signs were characterized by circling gait, pressing of head against fences or objects and motor incoordination. On gross examination of the brain the hemispheres were swollen, mainly the left one. On transversal sections, a 5cm X 7cm fluid-filled cyst was observed within the lateral ventricle of the left hemisphere. The cyst extended from the parietal to the occipital lobe, and compressed the third ventricle. There was also marked mid line deviation. Histologically, the brain lesion adjacent to the cyst, was characterized by a piogranulomatous process and vacuolization of neuropil. A diagnosis of equine hydatidosis caused by Echinococcus granulosus was made on the basis of the morphometric features of protoscolices hooks.